Food supply in the unoccupied territory of Belarus during the First World War - Motorova, Nadezhda S. (Journal of the Belarusian State University. History, 2022)
The article deals with the problem of organising food supply for the civilian population of unoccupied Belarusian provinces during the First World War. It is noted that in 1914 traditional method of price regulation through the issuance of rates was used to resolve it. Starting from 1915, food committees and commissions began to be created in the structure of the local self-government institutions to prevent shortage of goods and speculative trade. They were entrusted with the organisation of the purchase of food and its distribution, the maintenance of food warehouses and the development of rates. To provide financial support for their activities, there were used funds from local budgets and credits received from banks under the guarantees of the treasury or from government institutions. However, local authorities could not solve the problem of food supply for the civilian population effectively due to the lack of a unified concept of food policy at the state level and the lack of coordination between the actions of central departments. To the greatest extent, it manifested itself in the organisation of food supplies from the central regions of the Russian Empire to the front-line provinces. The Ministry of Agriculture of the Russian Empire, when determining the supply areas, did not coordinate the transportation plan with the War Ministry of the Russian Empire, which controlled the railways. The department also faced opposition from the Ministry of the Interior of the Russian Empire. It contributed food shortages, speculation and rising prices. As a result in late 1916 – early 1917 in the Belarusian provinces, not occupied by German troops, the food crisis worsened and turned into one of the main factors of destabilisation of the internal situation, which led to the February Revolution and a change in the state system.